A history of Russia from Peter the Great to Gorbachev - Steinberg, Mark D. 1953-; Teaching Company (Chantilly, VA Teaching Co., 2003)
Presents thirty-six lectures on the history of Russia by professor Mark Steinberg of the University of Illinois at Urbana-Champaign.
Part I. Lecture 1. Understanding the Russian past ; Lecture 2. The Russia of Peter the Great's childhood ; Lecture 3. Peter the Great's revolution ; Lecture 4. The age of empresses, Catherine the Great ; Lecture 5. Social rebellion, The Purgachev uprising ; Lecture 6. Moral rebellion, Nikolai Novikov ; Lecture 7. Alexander I, Imagining reform ; Lecture 8. The Decembrist rebellion ; Lecture 9. Nicholas I, Orthodoxy, autocracy, nationality ; Lecture 10. Alexander Pushkin, Russia's national poet ; Lecture 11. The birth of the intelligentsia ; Lecture 12. Westernizers, Vissarion Belinskii -- Part II. Lecture 13. Alexander II and the great reforms ; Lecture 14. "Nihilists" ; Lecture 15. Populists and Marxists ; Lecture 16. Paths to revolution, Lenin and Martov ; Lecture 17. Lev Tolstoy ; Lecture 18. The reign of Alexander III ; Lecture 19. Nicholas II, the last tsar ; Lecture 20. The revolution of 1905 ; Lecture 21. Peasant life and culture ; Lecture 22. The modern city and its discontents ; Lecture 23. Fin-de-si·ecle culture, Decadence and iconoclasm ; Lecture 24. Fin-de-si·ecle culture, The religious renaissance -- Part III. Lecture 25. War and revolution ; Lecture 26. Democratic Russia, 1917 ; Lecture 27. Bolsheviks in power ; Lecture 28. Civil war ; Lecture 29. Paths to socialism, the 1920s ; Lecture 30. Joseph Stalin ; Lecture 31. Stalin's revolution ; Lecture 32. Joy and terror, society and culture in the 1930s ; Lecture 33. The "great patriotic war" ; Lecture 34. The Soviet Union after Stalin ; Lecture 35. Private and public dissidence ; Lecture 36. Mikhail Gorbachev, Perestroika and Glasnost.
In 3 containers (26 cm.).
Teaching Co.: 8381--8383.
Mark Steinberg, lecturer.
Keywords: Russia -- History